2014
DOI: 10.5194/bg-11-3339-2014
|View full text |Cite
|
Sign up to set email alerts
|

Microbial responses to chitin and chitosan in oxic and anoxic agricultural soil slurries

Abstract: Abstract. Microbial degradation of chitin in soil substantially contributes to carbon cycling in terrestrial ecosystems. Chitin is globally the second most abundant biopolymer after cellulose and can be deacetylated to chitosan or can be hydrolyzed to N,N′-diacetylchitobiose and oligomers of N-acetylglucosamine by aerobic and anaerobic microorganisms. Which pathway of chitin hydrolysis is preferred by soil microbial communities is unknown. Supplementation of chitin stimulated microbial activity under oxic and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 82 publications
0
25
0
Order By: Relevance
“…Thus, although we did not detect chitinase genes in P. mirabilis SCDR1, the presence of Chitin-binding protein suggests that P. mirabilis SCDR1 has some mechanisms of protection against chitin and the chitosan antimicrobial effect. In addition, the presence of genes encoding for the members Chitosanase family GH3 of N, N′-diacetylchitobiose-specific 6-phospho-beta-glucosidase (EC 3.2.1.86), Beta N-acetyl-glucosaminidase (nagZ, beta-hexosaminidase) (EC 3.2.1.52), and Glucan endo-1, 4-beta-glucosidase (EC 3.2.1.-) in P. mirabilis SCDR1 suggests that it can hydrolyze chitosan to glucosamine [ 60 62 ]. This justifies the lack of antimicrobial effect of chitosan against P. mirabilis SCDR1.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, although we did not detect chitinase genes in P. mirabilis SCDR1, the presence of Chitin-binding protein suggests that P. mirabilis SCDR1 has some mechanisms of protection against chitin and the chitosan antimicrobial effect. In addition, the presence of genes encoding for the members Chitosanase family GH3 of N, N′-diacetylchitobiose-specific 6-phospho-beta-glucosidase (EC 3.2.1.86), Beta N-acetyl-glucosaminidase (nagZ, beta-hexosaminidase) (EC 3.2.1.52), and Glucan endo-1, 4-beta-glucosidase (EC 3.2.1.-) in P. mirabilis SCDR1 suggests that it can hydrolyze chitosan to glucosamine [ 60 62 ]. This justifies the lack of antimicrobial effect of chitosan against P. mirabilis SCDR1.…”
Section: Discussionmentioning
confidence: 99%
“…LEfSe analysis showed that the phyla Planctomycetes and Cyanobacteria were the preferential bacterial communities in OP soil. Members belonging to Planctomycetes have been reported as major groups to decompose heteropolysaccharide [39] and chitin [40] and are involved in the C cycle in soils, which might be related to the highest Ctot content being in OP soil. OTUs from Cyanobacteria are photoautotrophs and play key roles in biogeochemical processes in nature and improve the turnover of C and N in the soil [41].…”
Section: Differential Taxa For Cultivation Systemsmentioning
confidence: 99%
“…These cultured representatives, however, do not cover all planctomycete diversity in natural habitats. Recent molecular study of microbial degradation of chitin in an agricultural soil suggested involvement of Singulisphaera-like planctomycetes in this process (18). Additional evidence for the existence of chitinolytic planctomycetes was obtained in a metatranscriptome-based study of microbial populations driving biopolymer degradation in acidic peatlands (19).…”
mentioning
confidence: 97%